PERILAKU MAKAN DAN KEGIATAN PEKERJA WANITA DALAM HUBUNGANNYA DENGAN TINGKAT PRODUKTIVITAS KERJA - Uken S.S. Soetrisno; Rossi Rozanna; Gustina Sofia; Djoko Kartono; Almasyhuri Almasyhuri; Sri Murni Prastowo (Persagi, 1998)
This study evaluted nutrient intake and activity of female labors in relation to iron status and blood glucose level which may affect fitness and productivity. This study was part of the research on nutrition and health status during Ramadhan fasting in female labors. Total of 200 subjects, who were not lactating or pregnant, were evaluated for their anthropometry measurements, health status, hemoglobin and hematocrit levels. While 50 subjects were drawn as sub samples for evaluating their food consumption, daily activity, blood glucose level, fitness, and total patch clothes sown. Average energy intake was 142% of their RDA. Most of the labors used to have breakfast daily, which has an average of 30% of their total daily intake. The carbohydrate sources were mostly rice and instant noodles, while consumption of fruits and vegetables was limited and not so varied. Blood glucose was in normal level, while anemia due to low iron status was among 35% of the population. Their fitness was categorized as low, with total patch clothes sown was in the range of 36-46 unit per hour. In general they have to increase fruit and vegetable consumption, to anticipate the low intake of micro nutrients.Keywords: nutrient intake, activity, fitness, productivity, female labor